Associations between household environmental factors and immature mosquito abundance in Quetzaltenango, Guatemala - Zachary J. Madewell; Silvia Sosa; Kimberly C. Brouwer; José Guillermo Juárez; Carolina Romero; Audrey Lenhart; Celia Cordón-Rosales (BMC Public Health, 2019)
Abstract Background Aedes aegypti-borne diseases are becoming major public health problems in tropical and sub-tropical regions. While socioeconomic status has been associated with larval mosquito abundance, the drivers or possible factors mediating this association, such as environmental factors, are yet to be identified. We examined possible associations between proximity to houses and roads and immature mosquito abundance, and assessed whether these factors and mosquito prevention measures mediated any association between household environmental factors and immature mosquito abundance. Methods We conducted two cross-sectional household container surveys in February–March and November–December, 2017, in urban and rural areas of Quetzaltenango, Guatemala. We used principal components analysis to identify factors from 12 variables to represent the household environment. One factor which included number of rooms in house, electricity, running water, garbage service, cable, television, telephone, latrine, well, and sewer system, was termed “environmental capital.” Environmental capital scores ranged from 0 to 5.5. Risk factors analyzed included environmental capital, and distance from nearest house/structure, paved road, and highway. We used Poisson regression to determine associations between distance to nearest house/structure, roads, and highways, and measures of immature mosquito abundance (total larvae, total pupae, and positive containers). Using cubic spline generalized additive models, we assessed non-linear associations between environmental capital and immature mosquito abundance. We then examined whether fumigation, cleaning containers, and distance from the nearest house, road, and highway mediated the relationship between environmental capital and larvae and pupae abundance. Results We completed 508 household surveys in February–March, and we revisited 469 households in November–December. Proximity to paved roads and other houses/structures was positively associated with larvae and pupae abundance and mediated the associations between environmental capital and total numbers of larvae/pupae (p ≤ 0.01). Distance to highways was not associated with larval/pupal abundance (p ≥ 0.48). Households with the lowest and highest environmental capital had fewer larvae/pupae than households in the middle range (p < 0.01). Conclusions We found evidence that proximity to other houses and paved roads was associated with greater abundance of larvae and pupae. Understanding risk factors such as these can allow for improved targeting of surveillance and vector control measures in areas considered at higher risk for arbovirus transmission.